Highlighting Legal Aspects of Covid-19 Pandemic with Obligations and Duties of Government - Gholamreza Zakersalehi (Research Highlights in Disease and Health Research Vol. 5, 2023)
This chapter aims to highlight the Legal Aspects of Covid-19 Pandemic as well as some Obligations and Duties of Government in this period. Both legislation and supervision for the correct implementation of laws are the duty of governments. The special position of the government becomes more and more prominent in crisis conditions.